Surgical suture course for dental students with the Peyton-4-step approach versus the PDCA cycle using video assisted self-monitoring - A. Leitmann; Siegmar Reinert; Hannes Weise (BMC, 2020)
Abstract Background In this prospective study the Peyton 4-step approach of demonstration-deconstruction-comprehension (verbalization by the learner), and performance by the learner was compared to the PDCA cycle/Deming-Circle (Plan-Do-Check (video assisted self-monitoring)-Act) as a teaching method for surgical suturing and nodes with end performance as the primary objective. Methods Students of the third clinical semester in dental medicine were randomly selected to one of the two teaching methods. They completed a first course during the third clinical semester and a subsequent course during the fourth clinical semester. The focus was on learning surgical suturing techniques. Before the course started a questionnaire was handed out to both groups to evaluate their initial level of performance. Each course ended with a practical test to review the content of the course. The evaluation followed standardized parameters. Some of the test tasks in test one were repeated in test two to measure a horizontal as well as vertical difference in performance level. Results 53 students (Peyton: n = 28/18 female, 10 male; PDCA: n = 25/14 female, 11 male) have completed both courses. The evaluation of the subjective questionnaires showed that the members of the PDCA-groups achieved a higher subjective increase in performance. The objective results also indicated higher learning success in the PDCA-groups compared to the Peyton-Group. Discussion/Conclusion This study demonstrated significant learning success for both groups in their own self-assessment as well as in the results of the practical exercises. Subsequently, the superiority of the PDCA cycle could be shown for almost all criteria for surgical suturing techniques. Several studies prioritize the teaching of practical skills according to Peyton and consider step 3 ("comprehension") to be the essential factor. The PDCA cycle, which has its origins in industrial quality management, and its success can be understood from the perspective of learning theory in terms of Jean Piaget's model of equilibration. The necessity of active reflection on the learning content through practice constitutes the key element for transfer into long-term memory.